2020
DOI: 10.1167/jov.20.7.6
|View full text |Cite
|
Sign up to set email alerts
|

Using psychophysical performance to predict short-term ocular dominance plasticity in human adults

Abstract: Binocular rivalry has become an important index of visual performance, both to measure ocular dominance or its plasticity, and to index bistable perception. We investigated its interindividual variability across 50 normal adults and found that the duration of dominance phases in rivalry is linked with the duration of dominance phases in another bistable phenomenon (structure from motion). Surprisingly, it also correlates with the strength of center–surround interactions (indexed by the tilt illusion), suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 87 publications
3
13
1
Order By: Relevance
“…In healthy adults, a compelling example of short-term visual neuroplasticity can be induced by temporary monocular deprivation, typically with 2 to 2.5 hours of patching (Binda, Kurzawski, Lunghi, Biagi, Tosetti, & Morrone, 2018;Finn, Baldwin, Reynaud, & Hess, 2019;Lunghi, Burr, & Morrone, 2011;Lunghi, Burr, & Morrone, 2013;Lunghi et al, 2019;Lunghi, Emir, Morrone, & Bridge, 2015;Lunghi & Sale, 2015;Min, Baldwin, & Hess, 2019;Sheynin, Chamoun, Baldwin, Rosa-Neto, Hess, & Vaucher, 2019;Sheynin, Proulx, & Hess, 2019;Steinwurzel, Animali, Cicchini, Morrone, & Binda, 2020;Yao, He, Wang, Lu, Qu, Zhou, & Hess, 2017;Zhou, Clavagnier, & Hess, 2013;Zhou, Reynaud, & Hess, 2017), although the effects can be observed with shorter durations of occlusion (Min, Baldwin, Reynaud, & Hess, 2018). After patch removal, the deprived eye temporarily becomes more dominant.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy adults, a compelling example of short-term visual neuroplasticity can be induced by temporary monocular deprivation, typically with 2 to 2.5 hours of patching (Binda, Kurzawski, Lunghi, Biagi, Tosetti, & Morrone, 2018;Finn, Baldwin, Reynaud, & Hess, 2019;Lunghi, Burr, & Morrone, 2011;Lunghi, Burr, & Morrone, 2013;Lunghi et al, 2019;Lunghi, Emir, Morrone, & Bridge, 2015;Lunghi & Sale, 2015;Min, Baldwin, & Hess, 2019;Sheynin, Chamoun, Baldwin, Rosa-Neto, Hess, & Vaucher, 2019;Sheynin, Proulx, & Hess, 2019;Steinwurzel, Animali, Cicchini, Morrone, & Binda, 2020;Yao, He, Wang, Lu, Qu, Zhou, & Hess, 2017;Zhou, Clavagnier, & Hess, 2013;Zhou, Reynaud, & Hess, 2017), although the effects can be observed with shorter durations of occlusion (Min, Baldwin, Reynaud, & Hess, 2018). After patch removal, the deprived eye temporarily becomes more dominant.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed no (Brascamp, Becker, & Hambrick, 2018;Cao, Wang, Sun, Engel, & He, 2018) or only a weak (Steinwurzel, Animali, Cicchini, Morrone, & Binda, 2020) correlation in percept durations between binocular rivalry and structure-from-motion. This might imply that there are two independent rather than one shared control mechanism for inferences in binocular rivalry and structure-from-motion.…”
Section: Discussionmentioning
confidence: 96%
“…These studies suggest that one of the two surfaces in transparent motion is perceptually dominant and that perceptual biases in transparent motion might be related to biases in perceptual dominance in binocular rivalry. Second, several recent studies (Brascamp, Becker, & Hambrick, 2018;Cao, Wang, Sun, Engel, & He, 2018;Steinwurzel, Animali, Cicchini, Morrone, & Binda, 2020) compared the temporal aspects of multistability in binocular rivalry and structure-from-motion (Wallach & O'Connell, 1953), which is similar to transparent motion. Especially because these studies showed inconsistent evidence about the correlation in percept durations between binocular rivalry and structure-from-motion, we believe it is interesting to compare the two classes of stimuli also with respect to their spatial aspects, that is, their directional biases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we include a bistable structure-from-motion stimulus ( Figure 2 ). While correlated perceptual dynamics have been consistently observed for the combination of binocular rivalry and bistable plaid perception ( Brascamp et al., 2019 ; Cao et al., 2018 ; Sheppard & Pettigrew, 2006 ), this picture is less consistent for other combinations of bistable stimuli, including the combination of binocular rivalry and bistable structure-from-motion ( Brascamp et al., 2018 ; Cao et al., 2018 show no significant correlation, whereas Steinwurzel et al., 2020 show a positive correlation between switch rates in these two paradigms). Adding a structure-from-motion stimulus to our battery, therefore, allowed us to reexamine any correlation with the other bistable phenomena and, if it is observed, to test whether it is (partly) accounted for by variance in the strength of surround suppression.…”
Section: Introductionmentioning
confidence: 94%